Focusing on functional knee parameter determination to develop a better clinical gait analysis protocol - Leboucher, Julien; Salami, Firooz; Öztürk, Orhan; Heitzmann, Daniel; Götze, Marco; Dreher, Thomas; Wolf, Sebastian Immanuel (Gait & posture, 2021)
Background - Attempts to improve protocol standards of marker-based clinical gait analysis (CGA) have been one of the main focuses of research to enhance robustness and reliability outcomes since the 1990s. Determining joint centres and axes constitutes an important aspect of those protocols. Although the hip joint is more prominent in such studies, knee joint center (KJC) and axis (KJA) directly affect all outcomes. - Research question - What recommendations arise from the study of the scientific literature for determining knee joint parameters (KJP) for protocols of CGA? - Methods - A systematic, electronic search was conducted on November 2018 using three databases with the keyword combination (“functional approach” OR “functional method” OR “functional calibration”) AND (“hip joint” OR “knee joint” OR “ankle joint”) and analyzed by four reviewers. Given the existence of a recent review about the hip joint and the lack of material about the ankle joint, only papers about the knee joint were kept. The references cited in the selected papers were also screened in the final round of the search for these publications. The quality of the selected papers was assessed and aspects regarding accuracy, repeatability, and feasibility were thoroughly considered to allow for a comparison between studies. Technical aspects, such as marker set choice, KJP determination techniques, demographics, and functional movements, were also included. - Results - Thirty-one papers were included and on average received a rating of about 75 % according to the quality scale used. The results showed that functional methods are superior or equivalent to predictive methods to estimate the KJA, while a regression method was slightly better for KJC prediction. - Significance - Calibration methods should be applied to CGA whenever feasibility is reached. No study to date has focused on evaluating the in vivo RoM required to obtain reliable and repeatable results and future work should aim in this direction.
Available online 5 November 2020
Gesehen am 08.09.2021